Anharmonic Motion in the Crystal Structure of 2-Mercaptopyridone - Lutz, Martin; Smak, Tom J.; Sanderse, Arnaud T. (Crystals (Basel), 2022)
With the present study, we revise earlier results about the title compound 2-mercaptopyridone in which the deformation density was determined from an X–N study in 1982 (X-ray, neutron diffraction). In the current X–X study (X-ray, X-ray), anharmonic motion parameters for the atoms were included and it resulted in a very clean deformation density map without the unexplainable features of the literature results. The presence of anharmonic effects is supported by a study of the thermal expansion in the temperature range 100–260 K. A topological study of the electron density confirms a bond length alternation in the six-membered ring. The calculation of the electrostatic potential indicates that the N–H⋯S hydrogen bond is an electrostatic interaction, and that other attractive intermolecular contacts are probably dispersive.